Avaliação da maturidade internacional em empresas de serviços: proposição de um modelo aplicado - Nunes, Paola Waltrik (My University, 2025)
This Final Undergraduate Thesis analyzes the internationalization process of global service providers and/or service firms, proposing a model for assessing organizational maturity and monitoring the stages of internationalization projects. The research adopts a qualitative and exploratory approach, structured in two stages: a bibliographical and statistical review, followed by the application of the proposed maturity model through a questionnaire conducted with the case company, which specializes in international trade in services. The theoretical framework addresses the classical theories of internationalization, Dunning's OLI paradigm, and the Uppsala model, as well as contemporary approaches to born globals, linking them to the distinctions between the international trade of goods and services based on the inherent properties and/or characteristics of services. These characteristics are intrinsically connected to the service delivery modes established by the GATS (including an emerging fifth concept). This relationship is further elucidated through the concepts of Hard Services and Soft Services, highlighting their relevance for the strategic management of internationalization. Finally, the theoretical section presents a statistical overview of international trade in services in the global economy, followed by a regional contextualization and detailed analysis of Latin America and Brazil. The data collection instrument was developed based on the maturity model construction framework proposed by Röglinger and Pöppelbuß (2011), which is grounded in organizational maturity models such as CMM, BPMMM, BPMM, and PEMM, adapted to the reality of service firms and structured according to the dimensions and constructs validated in the study by Ortiz-Rojo and Vilela (2022).The results indicate that the analyzed company shows a good level of formalization in its international processes and demonstrates the applicability of the measurement tool. The study contributes to deepening knowledge about international trade in services and serves as a tool for monitoring internationalization projects, by proposing a maturity model that provides practical support for managers and entrepreneurs interested in enhancing their international readiness. [resumo fornecido pelo autor]
Este Trabalho de Conclusão de Curso analisa o processo de internacionalização de empresas prestadoras de serviços globais e/ou service firms, propondo um modelo de avaliação da maturidade organizacional e de monitoramento dos estágios dos projetos de internacionalização. A pesquisa adota abordagem qualitativa e exploratória, estruturada em duas etapas: revisão bibliográfica e estatística, e aplicação do modelo de maturidade proposto através de um questionário, junto a empresa case, especializada no comércio internacional de serviços. A fundamentação teórica aborda as teorias clássicas da internacionalização, o paradigma OLI de Dunning e o modelo de Uppsala, bem como as abordagens contemporâneas das born globals, atrelando-as às diferenciações do comércio internacional de bens e serviços a partir das propriedades e/ou características dos serviços, as quais estão intrinsecamente relacionadas aos modos de prestação de serviços estabelecidos pelo GATS (incluindo um quinto conceito emergente). Essa relação é melhor compreendida com os conceitos de Hard Services e Soft Services aqui abordados, evidenciando a relevância deste conhecimento para a gestão estratégica da internacionalização. Ao final do referencial teórico, acompanha-se um panorama estatístico do comércio internacional de serviços na economia mundial, seguido da contextualização regional, e detalhamento sobre a América Latina e Brasil. O instrumento de coleta foi desenvolvido a partir do framework de construção de modelo de maturidade de Röglinger e Pöppelbuß (2011), o qual fundamenta-se nos modelos de maturidade organizacional, como CMM, BPMMM, BPMM e PEMM, adaptado à realidade das empresas de serviços, com base nas dimensões e constructos validados no estudo de Ortiz-Rojo e Vilela (2022). Os resultados apontam que a empresa analisada apresenta bom grau de formalização de seus processos internacionais e demonstra aplicabilidade da ferramenta de mensuração. O estudo contribui para o aprofundamento dos conhecimentos sobre o comércio internacional de serviços e constitui uma ferramenta para monitoramento de projetos de internacionalização de empresas, ao propor um modelo de maturidade que fornece subsídios práticos para gestores e empreendedores interessados em aprimorar sua prontidão internacional. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Prestação de serviços; Globalização